2014
DOI: 10.1089/dia.2013.0155
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Glycemic Control Conditions in Relation to UrinaryN-Acetyl-β-d-Glucosaminidase in Patients with Type 2 Diabetes Mellitus Without Low Glomerular Filtration Rate

Abstract: These results suggest that postprandial hyperglycemia correlates with early renal tubule injury in type 2 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
3
4
0
Order By: Relevance
“…A small number of studies demonstrated a strong positive correlation between serum UA and 1,5‐AG levels . Yamanouchi et al and the authors of the present study have shown negative associations between urinary NAG (U/L) levels, urinary NAG‐creatinine ratio levels and serum 1,5‐AG. From the results of these studies, we are unable to exclude the possibility that 1,5‐AG was a mediator between the reduction in serum UA levels and treatment with SGLT2 inhibitors.…”
Section: Discussionsupporting
confidence: 62%
“…A small number of studies demonstrated a strong positive correlation between serum UA and 1,5‐AG levels . Yamanouchi et al and the authors of the present study have shown negative associations between urinary NAG (U/L) levels, urinary NAG‐creatinine ratio levels and serum 1,5‐AG. From the results of these studies, we are unable to exclude the possibility that 1,5‐AG was a mediator between the reduction in serum UA levels and treatment with SGLT2 inhibitors.…”
Section: Discussionsupporting
confidence: 62%
“…Damage of tubular 1,5‐AG reabsorption can likewise lead to changes in plasma concentrations. Various studies have demonstrated a correlation between the elimination of 1,5‐AG and markers of tubular damage . In the present study, urinary excretion of A1M as a marker of tubular damage did not differ in the various stages of CKD.…”
Section: Discussionsupporting
confidence: 57%
“…Various studies have demonstrated a correlation between the elimination of 1,5-AG and markers of tubular damage. [29][30][31] In the present study, urinary excretion of A1M as a marker of tubular damage did not differ in the various stages of CKD. Thus, an increase in the renal threshold because of older age or reduced renal function itself is probably the most important cause of the observed increase in 1,5-AG concentrations with declining kidney function.…”
Section: Discussionsupporting
confidence: 42%
“…The percentage of A isoform is the greatest in normal urine, and NAG isoenzymes A and B account for 80% to 90% and 10% to 20% of total NAG, respectively . In the past, we reported the association between urinary NAG and serum 1,5‐AG levels as a marker of postprandial glucose in patients with and without type 2 DM and between urinary NAG and plasma glucose levels at 120 minutes of the oral glucose tolerance test in prediabetes patients . Possibily, we investigated the relations with functional enzymuria stronger than lesional enzymuria.…”
Section: Discussionmentioning
confidence: 99%